Trace element dynamics of biosolids-derived microbeads. (May 2018) - Wijesekara, Hasintha; Bolan, Nanthi S.; Bradney, Lauren; Obadamudalige, Nadeeka; Seshadri, Balaji; Kunhikrishnan, Anitha; Dharmarajan, Rajarathnam; Ok, Yong Sik; Rinklebe, Jörg; Kirkham, M.B.; Vithanage, Meththika
Abstract: This study focused on quantifying and characterising microbeads in biosolids (i.e., treated sewage sludge), and in examining interactions of microbeads with trace elements when biosolids are added to soil. Under laboratory conditions, batch experiments were conducted to investigate the adsorption of Cu onto pure and surface modified microbeads suspended in soil. The ecotoxicity of microbead-metal complexes to soil microbial activities was also investigated by monitoring basal respiration and dehydrogenase activity. Concentrations of the microbeads were 352, 146, 324, and 174 particles kg −1 biosolids for ≤50, 50–100, 100–250, 250–1000 μm size fractions, respectively. The Scanning Electron Microscope (SEM) images illustrated wrinkled and fractured surfaces due to degradation. The adsorption of dissolved organic matter onto microbeads was confirmed through FT-IR microscopy, while using Inductively Coupled Plasma Mass Spectrometer (ICP-MS) the presence of trace metals including Cd (2.34 ng g −1 ), Cu (180.64 ng g −1 ), Ni (12.69 ng g −1 ), Pb (1.17 ng g −1 ), Sb (14.43 ng g −1 ), and Zn (178.03 ng g −1 ) was revealed. Surface modified microbeads were capable of adsorbing Cu compared to the pure microbeads, which may be attributed to the complexation of Cu with dissolved organic matter associated with the microbeads in the matrix. It was further revealed that the biosolids derived microbead-metal complexes decreased soil respiration (up to ∼ 26%) and dehydrogenase activity (up to ∼ 39%). Hence, microbeads reaching biosolids during wastewater treatment are likely to serve as a vector for trace element contamination, transportation, and toxicity when biosolids are applied to soil. Graphical abstract: Image 1 Highlights: Biosolids are a major source for microbeads in soil. A first-time study on microbial toxicity of biosolids-derived microbeads. Microbeads serve as a vector for transportation of trace elements in soil. Dissolved organic matter enhanced the adsorption of trace elements by microbeads. Microbeads decreased microbial respiration and dehydrogenase activity in soil.